A Hand Call Curriculum for Plastic Surgery Residents. Issue 12 (7th December 2021) - Bjorklund, Kim A.; Bourgeois, Tran; O'Brien, Meghan
Abstract : Background: The ability to diagnose and manage patients with acute hand injuries is an essential component of plastic surgery residency. This study proposes an innovative and feasible curriculum to improve hand surgery education for plastic surgery residents and ensure optimal care for patients with hand injuries. Methods: A hand call curriculum for plastic surgery residents (n = 29) from two institutions was implemented from 2018 to 2020. In 2018 and 2019, a hand call boot camp was conducted, while additional curricular sessions for anatomy and didactic learning were added in 2019–2020. Pre and post test assessments, as well as confidence assessments were conducted in 2018 and 2019. Results: In 2019, after having completed the boot camp, residents indicated significantly more confidence in identifying hand emergencies and formulating a basic treatment plan, including when to enlist help ( P = 0.0313). Overall, residents in earlier years (PGY 1–3) demonstrated steeper changes in confidence and readiness to take hand call than those in more senior years (PGY 4-8). Knowledge test scores improved amongst residents in both PGY groups following boot camp in both 2018 and 2019. Conclusion: Findings from our study will be used to optimize the hand call curriculum following limitations with COVID-19 and consider wider implementation across other plastic surgery programs nationally.